REVIVING ANCIENT INDIAN KNOWLEDGE SYSTEMS (AIKS) TO MITIGATE PERENNIAL FLOODING IN NORTHEAST INDIA: A SOCIO-ECOLOGICAL PARADIGM SHIFT - Huda, Eahya Al; Gogoi, Lakhimi; Bora, Jyotishmoy; Trangpoder, Ngawang Drema; Basumatary, Dulumoni; Patangia, Rosie; Talukdar, Jonali; Bora, Parineeta Saikia; Goswami, Parismita (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Northeast region of India (NEI), characterized by the Brahmaputra and Barak river systems, faces catastrophic annual flooding that destabilizes the economy, environment, and social fabric. Despite decades of modern engineering interventions—primarily embankments and large-scale dams—the frequency and intensity of floods remain unabated. This research paper explores the potential of Ancient Indian Knowledge Systems (AIKS) and indigenous ethno-hydrological practices as viable, sustainable alternatives or supplements to modern structural interventions. By analyzing Vedic hydrological principles, Kautilyan resource management, and the traditional wisdom of indigenous tribes (such as the Apatani and Mising), this paper argues for a transition from "flood control" to "flood adaptation." The study concludes that an integrated framework combining modern technology with AIKS can foster long-term resilience in the Brahmaputra basin.